Adaptation accuracy of milled lithium disilicate crowns: A 2D and 3D microCT analysis. Issue 4 (24th February 2020) - De Freitas, Bruna N.; Tonin, Bruna S. H.; Macedo, Ana P.; dos Santos, Thais M. P.; De Mattos, Maria d. G. C.; Hotta, Takami H.; Matsumoto, Wilson
Abstract: Objective: Evaluate the effects of the scanning techniques and the crystallization in the internal and marginal adaptation of milled lithium disilicate crowns by two techniques computer microtomography analysis. Materials and Methods: Sixteen polyurethane teeth prepared for a complete crown were divided into two groups according to the scanner method ( n = 8): indirect (IND), dental stone models were scanned with laser‐surface scanner, and direct (DIR), digital typodont creates with an intraoral scanner. Internal and marginal gap were evaluated by micro‐computed tomography (microCT). The replica technique (RT) was applied for analysis of total volume (TV) and marginal volume (MV) gap in microCT. The data showed normal distribution (Shapiro‐Wilk test). One‐way ANOVA (scanner techniques) with repeated measures (crystallization) was performed. Multiple comparisons were performed with Bonferroni adjustment ( α = .05). Results: The axial gap showed a significant difference between the times ( P = .017) for lower values after crystallization. The vertical marginal gap presented a significant difference in times for higher value after crystallization ( P = .001). The marginal horizontal gap IND was greater than DIR after crystallization ( P = .001) and IND before lower than after crystallization. For TV was not significant difference and MV in DIR was reduction ( P = .002) after crystallization. Conclusion: Crystallization changes the relationship between the crown and tooth, reducing internal gap and preventing the adequate fit in indirect and direct scanning. Clinical Significance: The measure gap under technological methodology is useful for adjust clinical parameters prosthetic in the CAD/CAM and the applicability of the new possibilities of analysis.